CAPABILITY IMPROVEMENT STRATEGY FASHARKAN MENTIGI TANJUNG UBAN TO SUPPORT INDONESIAN WARSHIP OPERATION IN SOUTH CHINA SEA - As'ad Aris Mustofa; Budisantoso Wirjodirjo; Arip Rivai (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
To support the readiness of KRI elements operating in the North Natuna sea area, one of them is needed by Fasharkan Mentigi Tanjung Uban which functions as a KRI maintenance and repair unit. Capacity building is needed, of course, through appropriate and appropriate strategies. By adopting the technometric method, it is hoped that the technology component with the largest gap between Fasharkan Mentigi Tanjung Uban and Fasharkan Surabaya will be obtained. Furthermore, using the SWOT method, a strategy will be formed according to the technology components. Interpretive structure modeling (ISM) method is used to obtain priorities and the relationship between strategies. The results of the analysis show that the Humanware Technology Component has the largest gap value between Fasharkan Mentigi Tanjung Uban and Fasharkan Surabaya, with a gap value of 0.1474, while the Technoware component gap is 0.0838, the infoware technology component gap is 0.0125 and the Orgaware technology component gap is 0.0099. The SWOT analysis provides 11 (eleven) development strategies according to the Humanware component, and the ISM method has provided 5 (five) hierarchical levels for these strategies. Keywords: Technometry, SWOT, ISM, Fasharkan